ANALISIS MODAL KERJA DAN PROFITABILITAS PADA PT. WAHANA SUMBER LESTARI SAMARINDA DI SAMARINDA - -, amad Munaji (EKONOMIA, 2014)
This study aimed to calculate and test the amount of working capital and profitability on PT. Wahana Sumber Lestari Samarinda. The problem in this study is â€œ"Is the increase in working capital in PT. Wahana Sumber Lestari Samarinda can increase profitability growth ?â€ Working capital is the total funds needed to generate income for the year or functional working capital or functional concepts. Profitability of a company shows a comparison between the earnings or capital assets that generate such profits, in other words, profitability is the ability of a company to generate profit for a certain period.Based on the analysis, working capital turnover at PT. Wahana Sumber Lestari SamarindaÂ  in 2009 only 2.5 times, in 2010 (2.8 times), in 2011 (2.9 times) and 2012 (2.6 times). Working capital turnover increased in 2010 and 2011 while in 2012 the working capital turnover has decreased. Overall value of working capital turnover is still below average that is 6 times the industry average or 60 days. The slow turnaround in the company's working capital caused by too much cash, inventory buildup and slow withdrawal of receivables.Profitability ratio in PT. Wahana Sumber Lestari Samarinda rides between 2009 and 2012 looks very volatile. Net Profit Margin, Return On Investment, Return On Equity, Growth Net Profit Margin, Return on Equity and Growth Growth Return On Investment had increased in 2010 then in 2011 and 2012 decreased. The decrease in 2011 and 2012 occurred because of decreased sales so little impact on net income. Despite an increase in 2010 than in 2009 but still below the value of the resulting average - the industry average is 20% net profit margin, return on investment 30% and 40% Return On Equity. (Kasmir, 2011:208). Profitability becomes a thing that is more important than just knowing the company earned net income.